Structure and Thermal Properties of Starch - Kalendová, Petra; Honcová, Pavla; Pulec, Vít; Svoboda, Ladislav (Česká společnost chemická, 2022)
The alkaline and water extraction of starch from chestnut (Aesculus hippocastanum) were optimized. The isolated starch was characterized using scanning electron microscopy, FTIR spectroscopy and thermogravimetric analysis. The thermogravimetric analysis had good potential for determination of amylose and amylopectin content in chestnut starch.
Struktura a tepelné vlastnosti škrobu
Keywords: starch; horse chestnut; thermal analysis; FTIR spectroscopy; škrob; kaštan koňský; termická analýza; FTIR spektroskopie